2016
DOI: 10.4236/ce.2016.715223
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Diversity in STEM: The Role of Drawing-Based Instruments

Abstract: Are drawing-based instruments such as the Draw-A-Scientist-Test (DAST) and its derivatives effective probes for assessing the images of scientists held by girls and children of diverse ethnicities in developed countries, children in Asia, and children in the developing world? This paper is a review of the literature from 2002 to the present designed to answer that question. It also addresses a second research question of what insights these images reveal that can inform development of inclusive science curricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In addition scientists are perceived as "male". There are researches in the literature indicating that engineers (Capobianco et al, 2011;Fralick et al, 2009;Ganesh, 2011;Koyunlu Unlu and Dokme, 2016;Park and Lee, 2014) and scientists (Barman et al, 1997;Bilen et al, 2014;Camcı Erdogan, 2013;Chambers, 1983;Fort and Varney, 1989;Fralick et al, 2009;Gonsoulin, 2001;Huang, Shih, Chen and Liu, 2015;Kara and Akarsu, 2013;Kaya et al, 2008;Kucuk and Bag, 2012;Losh, Wilke and Pop, 2008;McCann and Marek, 2016;Nuhoglu and Afacan, 2011;Ocal, 2007;Ozel, 2012;Ozel and Dogan, 2013;Ozgelen, 2012;Ozsoy andAhi, 2014, Turgut et al, 2017;Turkmen, 2008;Yontar Togrol, 2000;Yontar Togrol, 2013) are perceived as "male". Especially, as the class level of the girl students increases, female engineer and female scientist perception has decreased.…”
Section: Necatibey Eğitim Fakültesi Elektronik Fen Ve Matematik Eğitimentioning
confidence: 99%
“…In addition scientists are perceived as "male". There are researches in the literature indicating that engineers (Capobianco et al, 2011;Fralick et al, 2009;Ganesh, 2011;Koyunlu Unlu and Dokme, 2016;Park and Lee, 2014) and scientists (Barman et al, 1997;Bilen et al, 2014;Camcı Erdogan, 2013;Chambers, 1983;Fort and Varney, 1989;Fralick et al, 2009;Gonsoulin, 2001;Huang, Shih, Chen and Liu, 2015;Kara and Akarsu, 2013;Kaya et al, 2008;Kucuk and Bag, 2012;Losh, Wilke and Pop, 2008;McCann and Marek, 2016;Nuhoglu and Afacan, 2011;Ocal, 2007;Ozel, 2012;Ozel and Dogan, 2013;Ozgelen, 2012;Ozsoy andAhi, 2014, Turgut et al, 2017;Turkmen, 2008;Yontar Togrol, 2000;Yontar Togrol, 2013) are perceived as "male". Especially, as the class level of the girl students increases, female engineer and female scientist perception has decreased.…”
Section: Necatibey Eğitim Fakültesi Elektronik Fen Ve Matematik Eğitimentioning
confidence: 99%
“…Researchers who use the DAST ask students to “draw a scientist” and then assess those images based on seven stereotypical elements of scientists drawn from the literature: Lab coat, eyeglasses, facial hair, symbols of research (classified by size as small, medium, and large symbols), symbols of knowledge, technology, and relevant captions. Since its inception, the DAST has been administered to students of all ages to analyze their perceptions of scientists and has been used as a tool to evaluate interventions designed to change students’ perceptions of scientists (Finson, ; McCann & Marek, ). In 1995, Finson, Beaver, and Cramond added nine elements to the DAST, naming the checklist DAST‐C: Male, Caucasian, indications of danger, the presence of light bulbs, mythic stereotypes, indications of secrecy, working indoors, middle‐aged or elderly, and open comments.…”
Section: Introductionmentioning
confidence: 99%
“…Drawings by Turkish fifth graders portrayed Indications of Danger, Mythic Stereotypes, and Indications of Secrecy at frequencies of under 3% each (Türkmen, ). A literature review by McCann and Marek () suggests that DAST and DAST‐C results worldwide do not always reinforce the “monolithic” scientist stereotype due to the effect of students' culture (p. 2297).…”
Section: Introductionmentioning
confidence: 99%
“…Ahmad & Khan (2017) stated that the intensity of human belief would determine the eff ort to cope with diffi culties; the higher expected self-effi cacy would result in more active action. McCann & Marek (2016) indicated that elf-effi cacy was not the skill which could be possessed, but referred to individual belief in dealing with events with self-owned skills.…”
Section: Self-effi Cacymentioning
confidence: 99%